Retained plastic foreign body in the orbit after blunt trauma: A case report - Youssef Azouaghe; Abdelmonim Belkacemi; Saad Bouchlarhem; Achraf Amine Sbai; Drissia Benfadil; Azeddine Lachkar; Fahd El Ayoubi El Idrissi (Radiology Case Reports)
Intraorbital foreign bodies (IOFBs) are rare but potentially vision-threatening complications of orbital trauma, often presenting with subtle clinical signs despite significant underlying injury. We report the case of a 22-year-old male who sustained periorbital trauma after facial impact with a high-velocity plastic projectile. Clinical examination revealed a penetrating wound at the medial canthus of the left orbit, with preserved visual acuity and normal intraocular pressure. Computed tomography identified a radiopaque foreign body embedded in the inferomedial orbital floor. Surgical removal via a transconjunctival approach led to complete extraction of a spherical plastic object, with uneventful recovery and no postoperative complications. This case underscores the diagnostic challenges posed by nonmetallic IOFBs and the critical role of CT imaging in orbital trauma. Management strategies depend on the nature, size, and location of the foreign body, as well as associated complications such as globe perforation, infection, or oculomotor dysfunction. Prompt surgical intervention is essential to prevent long-term ocular and functional sequelae.